Pulses - Boon for Human and Soil Health - Ranjith, M.; Sridevi, S. (Chronicle of Bioresource Management, 2023)
Pulses, the food legumes, are being grown by farmers since millennia and provide nutritionally balanced food to the people. Pigeonpea, blackgram, greengram, lablab bean, moth bean, and horsegram have originated and domesticated in the Indian subcontinent. These are rich source for vegetable proteins, fibre, iron, potassium, folate and antioxidants. Further, they are free from cholesterol and gluten. They have definite role in the prevention and management of chronic diseases such as diabetes, coronary conditions and cancer. They are grown as cover/inter crops and able to fix atmospheric nitrogen, sequester carbon into the soil, suppress the weeds and control soil erosion from the splash detachment thus protects soil health. Emissions of greenhouse gases soil and water pollution can be reduced through inclusion of pulses in cropping systems thus assures ecologically sustainable agriculture. Proper policy support to encourage the pulse production is the need of the hour.